Diastereoselective synthesis of 3, 3-disubstituted 3-nitro-4-chromanone derivatives as potential antitumor agents. Issue 5 (14th January 2019) - Chen, Huiqing; Xie, Jia; Xing, Dong; Wang, Jinping; Tang, Jie; Yi, Zhengfang; Xia, Fei; Qiu, Wen-Wei; Yang, Fan
Abstract : We report an efficient and highly diastereoselective protocol for the rapid construction of 3-nitro substituted 4-chromanones by an intramolecular Michael-type cyclization of α-nitro aryl ketones bearing unsaturated ester units. Abstract : We report an efficient and highly diastereoselective protocol for the rapid construction of 3-nitro substituted 4-chromanones by an intramolecular Michael-type cyclization of α-nitro aryl ketones bearing unsaturated ester units. A catalytic amount of KO t Bu was found to be crucial for the high diastereoselective control of this transformation. With this protocol, a series of 3, 3-disubstituted 3-nitro-4-chromanones were synthesized in good to excellent yields with high diastereoselectivities and showed moderate to good in vitro antitumor activities, representing promising antitumor hits for further drug discovery.